2015
DOI: 10.1088/2050-6120/3/4/042004
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent dyes with large Stokes shifts for super-resolution optical microscopy of biological objects: a review

Abstract: The review deals with commercially available organic dyes possessing large Stokes shifts and their applications as fluorescent labels in optical microscopy based on stimulated emission depletion (STED). STED microscopy breaks Abbe's diffraction barrier and provides optical resolution beyond the diffraction limit. STED microscopy is non-invasive and requires photostable fluorescent markers attached to biomolecules or other objects of interest. Up to now, in most biology-related STED experiments, bright and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
177
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(192 citation statements)
references
References 120 publications
3
177
0
5
Order By: Relevance
“…On the other hand, the 2‐thien‐3‐yl‐substituted dipyrrin 8 shows slightly blue‐shifted values compared to 6 . The fairly large Stokes shifts of all dipyrrins in the range of 2000–2700 cm −1 make these compounds interesting for many applications . To our surprise, only a few studies on the fluorescence of dipyrrins are reported …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the 2‐thien‐3‐yl‐substituted dipyrrin 8 shows slightly blue‐shifted values compared to 6 . The fairly large Stokes shifts of all dipyrrins in the range of 2000–2700 cm −1 make these compounds interesting for many applications . To our surprise, only a few studies on the fluorescence of dipyrrins are reported …”
Section: Resultsmentioning
confidence: 99%
“…Large Stokes shift fluorophores are advantageous for accurate fluorescence measurements (i.e., no excitation light is measured with emitted light) and avoiding self‐quenching. They are also interesting for bioimaging with lower background interference and particularly for multicolor imaging in super‐resolution optical microscopy, where the number of detection channels can potentially be reduced thanks to a facilitated spectral separation (in excitation or emission) with more common small Stokes shift dyes . For instance, combining two fluorophores with distinct absorptions, yet a similar emission, can lead in stimulated emission depletion (STED) microscopy to employing only one depletion wavelength, thereby simplifying the overall setup.…”
Section: Introductionmentioning
confidence: 99%
“…With the latest advancements in the field of fluorescent microscopy, an increasing number of efforts are made to develop bright, photostable, nontoxic fluorescent dyes that can bind to particular targets with high specificity . Additional features such as fluorogenicity or environment sensitivity may further enhance efficiency of the labeling by reducing background signals .…”
Section: Introductionmentioning
confidence: 99%